I concerti per due violini di Vivaldi (con edizione di RV 513, 521, 528, 764 e ricostruzione di RV 520, 526) - Ammetto, Fabrizio <1965> (Alma Mater Studiorum - Università di Bologna, 2010)
In the whole of Europe the most important composer of concertos for two violins is indubitably Vivaldi (1678-1741), who produced almost thirty works of this type during almost the full length of his creative career. The dissertation examines this particular side of Vivaldi’s activity, starting with an examination of the concerto in Rome, Bologna, and Venice at the turn of the seventeenth and eighteenth centuries. The aspects investigated include the ‘conceptual’ origins of the double concerto for two violins in Vivaldi, the nature, distribution and interrelationship of their sources (particular attention being given to compositional revisions in the autograph manuscripts) and an analysis of the works themselves that takes in form, tonal structure, technical-instrumental character and performance practice. The concertos that have come down in particularly problematic non-autograph sources are discussed in detail and presented in critical editions. A reconstruction is offered of the two works (RV 520 and 526) that have survived only in incomplete form, lacking the part of the first soloist. The concertos for two violins composed in Germany by Telemann and J. S. Bach, the contemporaries of Vivaldi who paid greatest attention to the double concerto genre, are then described and analysed. The thesis ends with a complete list of modern editions of Vivaldi’s concertos for two violins and a select discography.